Magnetic Coupling between the Interior and Atmosphere of the Sun - Hasan, S.; Rutten, R. J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
These are the proceedings of the conference on Magnetic Coupling between the Interior and the Atmosphere of the Sun held December 2-5, 2008, which was planned to coincide with the centenary of the discovery of the Evershed effect at Kodaikanal in 1909. The aim of this meeting was to bring a critical focus to the comprehensive understanding of the important issues pertaining to solar magnetism, with particular emphasis on the various MHD processes that operate in the solar atmosphere. The participants reviewed the current status of magnetic field measurements and their implications with regard to recent theories and numerical models that address the fundamental scales and processes in the highly magnetized, turbulent plasma. The conference also provided a platform for in-depth discussions of new results from various space missions, as well as a comparison with ground-based observing facilities such as the Swedish 1-m Solar Telescope.
Preamble -- Republication of: Radial Movement in Sunspots -- Opening Remarks -- Solar Physics at the Kodaikanal Observatory: A Historical Perspective -- Vainu Bappu Memorial Lecture: What is a Sunspot? -- Oral Presentations -- Angular-Momentum Coupling Through the Tachocline -- Outstanding Issues in Solar Dynamo Theory -- Status of 3D MHD Models of Solar Global Internal Dynamics -- Measuring the Hidden Aspects of Solar Magnetism -- Recent Advances in Chromospheric and Coronal Polarization Diagnostics -- Probability Density Functions to Represent Magnetic Fields at the Solar Surface -- Spectropolarimetry with CRISP at the Swedish 1-m Solar Telescope -- Spectropolarimetry with the NLST -- Magnetic Coupling in the Quiet Solar Atmosphere -- The Evershed Effect with SOT/Hinode -- The Evershed Flow and the Brightness of the Penumbra -- A Topology for the Penumbral Magnetic Fields -- Theoretical Models of Sunspot Structure and Dynamics -- Convection and the Origin of Evershed Flows -- The Magnetic Field of Solar Spicules -- Three-Dimensional Magnetic Reconnection -- Signatures of Coronal Heating Mechanisms -- Waves in Polar Coronal Holes -- MHD Wave Heating Diagnostics -- Coronal Mass Ejections from Sunspot and Non-Sunspot Regions -- CME Observations from STEREO -- Low-Frequency Radio Observations of Coronal Magnetic Fields -- Evolution of Near-Sun Solar Wind Turbulence -- The Solar-Stellar Connection -- Summary and Perspective -- Poster Presentations -- Evidence for Return Meridional Flows in the Convection Zone -- Long-Term Variations in Meridional Flows -- Low-Degree High-Frequency and Modes in the Solar Core -- Interior and Exterior Clues of Solar Activity -- Do Active Regions Modify Oscillation Frequencies? -- Deep-Focus Diagnostics of Sunspot Structure -- Are Polar Faculae Generated by a Local Dynamo? -- The Hanle Effect as Diagnostic Tool for Turbulent Magnetic Fields -- Phase III of the USO Solar Vector Magnetograph -- Revisit of the Classic Wilson Effect -- The Waldmeier Effect in Sunspot Cycles -- Flare-Driven Acoustic Modes in the Sun -- Dynamics of Active Regions Revealed by Tracking of Doppler Features -- The Growth of a Primitive Penumbra -- Evershed Flow Velocities During 100 Years -- The Thermal Structure of Sunspots -- Bright Points in G-Band and Ca IIH Images from Hinode -- Waves in the Transition Region -- Viscous Damping of Alfvén Surface Waves with Steady Flows -- Statistical Detection of Propagating Waves in a Polar Coronal Hole -- Network Loop Oscillations with EIS/Hinode -- Dynamical Evolution of X-Ray Bright Points with Hinode/XRT -- Helicity at Photospheric and Chromospheric Heights -- Evolution of Coronal Helicity in a Twisted Emerging Active Region -- Power-Law Nanoflare Heating -- Spectroscopic Diagnostics of Polar Coronal Plumes -- A Flaring Polar Filament -- Solar X-Ray Processes -- Time-Varying Thermal Emission in Solar Flares -- Multi-Wavelength View of Flare Events on 20 November 2003 -- Time-Delay Between Solar Soft X-Ray and EUV Flare Emissions -- Major Surge Activity of Super-Active Region NOAA 10484 -- Coronal Magnetic Field Estimation Using Type-II Radio Bursts -- Acceleration of CMEs Associated with Eruptive Prominences -- Interplanetary Consequences of a Large CME -- Solar System Resonances on Light-Travel Time Scales Set Up before Proto-Sun s Nuclear Ignition -- Summaries of Presentations Published Elsewhere -- Cycle Prediction from Dynamo Theory -- Why Does the Torsional Oscillation Precede the Sunspot Cycle? -- The Subsurface Magnetic Structure of Solar Active Regions -- Sunspot Magnetometry from Kodaikanal -- Vector Magnetic Field in Emerging Flux Regions -- Evolution of Umbral Dots and Penumbral Grains -- Strong, Localized Downflows in a Sunspot Light Bridge -- Small-Scale Velocities in Sunspot Penumbrae -- Photospheric Temperatures from Ca IIH -- Dual-Line Spectral Imaging of the Chromosphere -- Inversions of High-Cadence SOLIS-VSM Stokes Observations -- Flows in Flaring and Dormant Active Regions -- Magnetic and Velocity Field Changes Related to the Solar Flares of 28 and 29 October 2003 -- A Numerical Investigation of Unsheared Flux Cancelation -- Wave Heating of Coronal Loops with Steady Flows -- Damping of Prominence Oscillations in Steady Equilibrium -- Variation of Network Contrast with Height -- A Flaring Twisted Emerging Flux Region -- Evidence of Magnetic Reconnection Outflows in a Flare seen by Hinode/EIS -- Does Coronal Rotation Period Depend on the Sunspot Number? -- Coronal Magnetic Field from an Extreme Radio Burst -- CME Kinematics and Dynamics -- Solar Wind Monitoring with SWIM-SARA Onboard Chandrayaan-1 -- Coupling of the Solar Wind and the Magnetosphere -- The FIP Effect in RV Tauri Stars.
Keywords: Physics; Physics; Astrophysics and Astroparticles